Jurisprudential Implications for the Right of Mut'ah in Divorce at the Wife's Initiative - Habibah, Zahrotul; Ali , M. Su'udi; Maulana Ahmad , Ilma (Hakamain: Journal of Sharia and Law Studies, 2025)
This research aims to examine the role of jurisprudence in fulfilling the right to mut’ah in divorce cases initiated by the wife, particularly in the context of family law reform. The issue is significant because the obligation to provide mut’ah has traditionally been subjectively limited to divorces initiated by the husband, creating normative constraints for wives who file for divorce. This study employs a juridical-normative research design, using legislative and case approaches to analyze court decisions and legal norms governing mut’ah. The findings demonstrate that jurisprudence plays a strategic role as a legal precedent, a mechanism for filling normative gaps, and a driver of progressive interpretation in family law. The analysis reveals that mut’ah rights may still be granted in wife-initiated divorces when the wife is proven not to be in a state of nusyuz. Furthermore, the study identifies two practical strategies used by wives to obtain mut’ah before the Religious Court, namely by explicitly claiming it in the petitum and through mutual agreement achieved in mediation proceedings. The research contributes to strengthening normative access to mut’ah rights and provides